A Causal Model of Motivational Beliefs with the Mediating Role of Academic Hope on Academic Self-Efficacy in High School Students - Lida Esmaeili; Nadereh Sohrabi; Amir Houshang Mehryar; Mohammad Khayyer (Iranian Evolutionary Educational Psychology Journal, 2019)
The purpose of this study was to explain the causal model between motivational beliefs and self-efficacy with the mediating role of academic hope in high school students. The research method was descriptive and correlational.  The sample size was 558 (248 girls and 310 boys) from high school students (tenth, eleventh and twelfth grade) in Shiraz, Iran in 1997-98. They were selected through multistage cluster sampling method. The tools used in this research included Pintrich and De Groot self-regulation learning strategies scale; Sohrabi and Samani academic hope scale and Gink and Morgan student self-efficacy scale. LISREL software was used for statistical calculations. Path analysis was used for data analysis that showed the academic hope plays a significant mediating role in the relationship between motivational beliefs and academic self-efficacy. Also, results indicated the proposed model has the good fitting indices. Generally the results revealed the role of motivational variables in self-efficacy.